A PETROGRAPHICAL REVIEW OF METAMORPHIC ROCKS FROM CILETUH COMPLEX, IN WEST JAVA AND THEIR RELATED METAMORPHISM IN CENTRAL INDONESIA REGION - Prasetyo, Anton; Romora S, Jordan; Yeftamikha, .; Fransiskus L. B, .; Imam S, Nugroho (DEPARTEMEN TEKNIK GEOLOGI FT UGM, 2016)
Ciletuh Complex is considered to be one among other localities (Luk Ulo, Bantimala, Meratus Complexes) in Indonesia in which Cretaceous subduction fossil was occurred. The objective of this study is determining the variation of metamorphic rocks in Ciletuh Complex by petrographical analysis through their texture and mineral assemblages. Metamorphic rocks in Ciletuh Complex were collected in Gunung Badak and Tegal Pamidangan areas. Based on petrographical analysis, metamorphic rocks in Gunung Badak area consist of Grt-Ms-Qz schist, Ms phyllite, quartzite and serpentinite. Meanwhile in Tegal Pamidangan area, consist of Ms-Qz phyllite and slate. The metamorphic rocks indicate low-grade metamorphism in the greenschist-facies. The protolith of metamorphic rocks are suggested from pelitic, ultramafic, and quartz-rich rocks. Present study did not recognize the blueschist or eclogites-facies rocks which indicates high-pressure and low-temperature metamorphism in the subduction system. The present of serpentinite among the low-grade metamorphic rocks indicates that metamorphic environment still correlate with oceanic crust environment or mantle. Low-grade metamorphic rocks might be developed on the near surface of the subduction system. Keywords : petrography analysis, mineral assemblages, metamorphic facies, protolith